Analysis of the Immediate Effects of the LaxVox Technique on Digital Videokymography Parameters in Adults With Voice Complaints. - Nogueira do Nascimento, Ualisson; Santos, Marco Aurélio Rocha; Gama, Ana Cristina Côrtes (Journal of Voice, 2025)
Digital videokymography based on high-speed videoendoscopy enables the evaluation of therapeutic techniques and voice training, such as the LaxVox technique, on vocal fold vibrations. This study investigated the immediate effects of the LaxVox technique on digital videokymographic parameters obtained through high-speed videolaryngoscopy in adults with voice complaints. An experimental intrasubject comparative study of adults with voice complaints was conducted. Image processing software was used to analyze the videos and obtain digital videokymography parameters. The intraclass correlation coefficient was used to determine the intra-rater reliability of the analyzed parameters. The paired t test and Wilcoxon signed-rank test were used to compare digital videokymography parameters before and after the LaxVox technique, in sex-specific analyses. The significance level was set at 5%. In total, 25 laryngeal images from 15 women and 10 men were analyzed. On digital videokymography analysis, the mean vocal fold opening in the posterior glottal region was decreased immediately after using the LaxVox technique in women. In contrast, no significant changes were found in other parameters compared to pre LaxVox technique values in both men and women with voice complaints. Digital videokymography analysis revealed that the LaxVox technique reduces the mean vocal fold opening in the posterior glottal region of women with voice complaints.